Learning Curve and Comparison of Dynamic Implant Placement Accuracy Using a Navigation System in Young Professionals - Johannes Spille; Eva Helmstetter; Paul Kübel; Jan-Tobias Weitkamp; Juliane Wagner; Henning Wieker; Hendrik Naujokat; Christian Flörke; Jörg Wiltfang; Aydin Gülses (MDPI AG, 2022)
The aim of the current study was to evaluate the learning curve and accuracy of implant placement by young professionals using a dynamic computer-assisted surgical system for dental implant placement. Ten students tried to place eight implants with a dynamic surgical system in predefined positions on two consecutive weekends, resulting in 160 implant placements in total. Postoperatively, the positions of the implants were scanned with an intraoral scanner and compared for deviations at the entry point, the apex, as well as angular deviations to the master model. The mean values of all measurements improved; statistical significance was found for the changes in the angle as well as for the position of the implants to the apex (p < 0.001). Furthermore, the young professionals indicated subjective improvement in handling the dynamic surgery system. Navigated surgical dental implant placement can be learned quickly and can support young professionals in everyday clinical practice, especially in difficult anatomic situations.